Social Capital And Civil Participation In The Development Of Village Tourism Area In Lombok - Wahid, Abdul; Destrity, Nia Ashton (Journal of Politics and Policy, 2020)
The development of tourism villages is in line with the management of social capital in the community. This study aims to reveal how social capital and citizen participation contribute to the development of Central Lombok tourism. In-depth interviews and observations were usedÂ  purposively on the headman and manager of the tourism village in the Sade and Stanggor village, Central Lombok. This study found that the progress of the management of this tourism village cannot be separated from the social capital owned by the community and its management. The management of the tourism village is determined by leadership, culture, awareness, and participation of the tourism village community (community based development). Leadership is an important factor as a motor of participation and a guardian of shared values. Culture that is reflected in the architecture of buildings, traditional ceremonies, arts and literature, and crafts are part of the basic capital of tourism. This strong modality makes the tourism village accepted because it is considered to provide material benefits for residents. The study of tourism villages in this research focuses on the management of tourism villages by the community and local village officials. In fact, the development of tourism villages is inseparable from the macro policies of the central and regional governments. Therefore, a study of the form of policy and its influence on the development of tourism villages can be examined in further research.Keywords: social capital, tourism, community based development.